Human Rights , nature , origin , development and importance - Vora Geetaben Tulasibhai (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2021)
In order to maintain human dignity and achieve human progress certain such rights should be given to human beings , as may not require any approval of the state . These are fundamental human rights . Prior to the formation of the United Nations Organization , the League of Nations had done an admirable work in respect of human rights . A committee was set up under the Presidentship of Mrs. Roosevelt to prepare a draft of the human rights . The Report submitted by this committee was accepted by the General Assembly of the U.N.O. with some amendments and thus the human rights were approved on 10 th December 1948. Since onwards the 10th December is celebrated as the Day of Human Rights in the world .